Increased red cell distribution width in Fanconi anemia: a novel marker of stress erythropoiesis. Issue 1 (December 2016) - Sousa, Rosa; Gonçalves, Cristina; Guerra, Isabel; Costa, Emília; Fernandes, Ana; do Bom Sucesso, Maria; Azevedo, Joana; Rodriguez, Alfredo; Rius, Rocio; Seabra, Carlos; Ferreira, Fátima; Ribeiro, Letícia; et al.
Abstract Background Red cell distribution width (RDW), a classical parameter used in the differential diagnosis of anemia, has recently been recognized as a marker of chronic inflammation and high levels of oxidative stress (OS). Fanconi anemia (FA) is a genetic disorder associated to redox imbalance and dysfunctional response to OS. Clinically, it is characterized by progressive bone marrow failure, which remains the primary cause of morbidity and mortality. Macrocytosis and increased fetal hemoglobin, two indicators of bone marrow stress erythropoiesis, are generally the first hematological manifestations to appear in FA. However, the significance of RDW and its possible relation to stress erythropoiesis have never been explored in FA. In the present study we analyzed routine complete blood counts from 34 FA patients and evaluated RDW, correlating with the hematological parameters most consistently associated with the FA phenotype. Results We showed, for the first time, that RDW is significantly increased in FA. We also showed that increased RDW is correlated with thrombocytopenia, neutropenia and, most importantly, highly correlated with anemia. Analyzing sequential hemograms from 3 FA patients with different clinical outcomes, during 10 years follow-up, we confirmed a consistent association between increased RDW and decreased hemoglobin, which supports the postulated importance of RDW in the evaluation of hematological disease progression. Conclusions This study shows, for the first time, that RDW is significantly increased in FA, and this increment is correlated with neutropenia, thrombocytopenia, and highly correlated with anemia. According to the present results, it is suggested that increased RDW can be a novel marker of stress erythropoiesis in FA.